Pharmacokinetics of cefazolin for prophylactic administration to dogs - González-Cintrón, Omar J. (Kansas State University, 2017)
OBJECTIVE: The purpose of the study reported here was to evaluate pharmacokinetics of cefazolin in dogs receiving a single IV injection of cefazolin (22 mg/kg) and dogs receiving simultaneous IV and IM injections of cefazolin (total dose, 44 mg/kg). METHODS: Twelve purpose-bred Beagles (6/group) were assigned to receive a single injection of cefazolin (22 mg/kg, IV) or simultaneous injections (22 mg/kg, IV, and 22 mg/kg, IM). Interstitial fluid was collected over a 5-hour period using ultrafiltration probes for pharmacokinetic analysis. RESULTS: Mean cefazolin concentration in the interstitial fluid at 1, 1.5, 2, 3, 4, and 5 hours after injection was 39.6, 29.1, 21.1, 10.3, 6.4, and 2.7 μg/mL, respectively, for the IV group and 38.3, 53.3, 46.4, 31.7, 19.1, and 8.9 μg/mL, respectively, for the IV + IM group. The mean area under the concentration-time curve extrapolated to infinity, maximum concentration, half life and time to the maximum concentration was 74.99 and 154.16 h•μg/mL, 37.3 and 51.5 μg/mL, 0.96 and 1.11 hours, 1.28 and 1.65 hours, respectively, for the IV and IV + IM groups. CONCLUSIONS AND CLINICAL RELEVANCE: Cefazolin concentrations in interstitial fluid of dogs were maintained at > 4 μg/mL for 4 hours after a single IV injection and for 5 hours after simultaneous IV and IM injections. Based on these results, simultaneous administration of cefazolin IV + IM 30 to 60 minutes before surgery should provide interstitial fluid concentrations effective against the most common commensal organisms (Staphylococcus spp and Streptococcus spp) on the skin of dogs for surgical procedures lasting ≤ 4 hours.
Keywords: Pharmacokinetics; Cefazolin; Antibiotic; Surgery; Dog